EMERGENCE RESISTANT UROPATOGEN Escherichia coli SETELAH PEMBERIAN SIPROFLOKSASIN DAN -MANGOSTIN SECARA in vitro - Maya Dian Rakhmawatie; Afiana Rohmani (Universitas Muhammadiyah Semarang, 2015)
Emergence resistant on uropatogen Escherichia coli can occur shortly after the start of therapy using subtherapeutic doses of ciprofloxacin. Ciprofloxacin is an antibiotic that works depends on the level of concentration, higher ratio Cmax / MIC will give increases in effectiveness. When the ratio of Cmax / MIC <1, then the risk of emergence resistant will be increased. One of the herbs that are abundant in Indonesia and has anti-bacterial activity is mangosteen (Garcinia mangostana L.), which has an active compound -mangostin. Administration of the active compound α-mangostin is expected to help prevent the emergence resistant of uropatogen E. coli due to the use of subtherapeutic ciprofloxacin. This research was conducted by giving treatment to uropatogen E. coli in vitro. Bacterial strains used are uropatogen E. coli resistant to ciprofloxacin with MIC values of 128 μg / mL. Treatment is divided into (I) treatment groups using ciprofloxacin concentration Cmax at a dose of 750 mg (4.3 μg / mL), (II) treatment groups using ciprofloxacin concentration of 4.3 μg / mL and -mangostin 0.18 μg / mL, and (III) the negative control group. The study states that the administration of the combination of α-mangostin and ciprofloxacin delayed the growth of uropatogen E. coli resistant strains (MIC value of 128 μg / mL) compared to administration of ciprofloxacin alone (p 0.000). But the combination of α-mangostin and ciprofloxacin can not prevent an increased in resistance strain uropatogen E. coli, which is characterized by an increased in the value of the MIC to be 256 μg / mL after 2 hours of treatment.Keywords: ciprofloxacin, resistance, -mangostin, uropatogen E. coli